REDESIGN THE UI/UX OF THE PT MNO COMPANY PROFILE WEBSITE USING THE THINKING DESIGN METHOD - Putera, Ihsan; Wati, Emma Nor Kholida; Natasia, Sri Rahayu; Laia, Yonata (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
In the current era of globalization, large and small companies must develop strategies for using websites to improve business branding to the general public. Based on the results of problem identification, there are several UI/UX problems on the PT MNO website, including an unattractive appearance, messy and overlapping fonts, and a messy layout. This research aims to redesign the PT MNO website to improve its UI/UX to make it more informative, clear, and easy to use. The solution can be implemented by redesigning the website design for PT MNO utilizing the design thinking methodology. This method has five phases: Empathize, define, imagine, prototype, and test. Based on observations and interviews, three categories of problems in the current website category were found: content, navigation, and features. Then, five pages were created for the design results or mockup solutions, namely the home page, services, portfolio, programs, and about us. Testing used a usability metric, SEQ (Single Ease Question). Based on SEQ theory, if the results given by respondents are more than 5.5, then the task or scenario is considered successful or easy to do. So, the five functions in terms of convenience were easy for the five respondents to complete. Keywords: Design Thinking, Redesign, UI/UX, Website.